Acumulação de competências tecnológicas e os processos subjacentes de aprendizagem na indústria eletrônica de consumo: o caso da SHARP do Brasil S/A - Mota Junior, Leônidas Ferreira da (2002)
This dissertation studies the relationship between the accumulation of technological competences and the underlying processes of learning. The study of this relationship was examined in the factory of consumption electronics Sharp of Brasil SI A, located in the city of Manaus, during the period from 1972 to 2000. The accumulation and sustentation of technological competences are developed through learning processes in the organizations. The learning processes are related directly to the tax of accumulation of technological competences of the organizations. The dissertation, using the structure of existent analysis in the literature, examines the learning processes using four characteristics: variety, intensity, operation and interaction. The accumulation of competences is analyzed starting from two technological functions: process/organization and products. Along the analyzed period, the company accumulated different leveIs of technological competences and with varied speeds in the studied functions. In the decade of 80, the company through a better coordination of efforts, started to acquire and to convert individual knowledge into organizational knowledge, accelerating the growth of the tax of accumulated technological competences. Still in the end of the decade 80, the company was capable to accumulate innovative competences in the two studied functions. The accumulation of technological competences is a important aspect to competitiveness and survival of the organizations. However, only the accumulation of technological competences doesn't guarantee the good acting and the survival of the organization. The studied company, in spite of the accumulation high leveIs of technological competences along the period, faces a great financiaI crisis. The conclusion of this dissertation suggests that the tax of the accumulation of technological competences can be explained by the capacity of the company in socialize and codify the individual learning, acquired from externaI and internaI processes of learning applied in a continuous and organized way, converting in organizational learning.